Prof. Dr. KH. Ali Mustafa Yaqub, MA. : Muhaddis Nusantara Bertaraf Internasional - Nasrullah Nurdin (Jurnal Lektur Keagamaan, 2016)
In Indonesia, Hadith studies are a rare discipline, if not a very rare one. This raises a lot of concerns within the Muslim community about the frequent use of false (maudhû '), semi-fake (matrûk), and weak (dha'īf) Hadiths, or claiming things that are not as part of Prophetic traditions. This article attempts to review the scholarly background, the ideas, and the scientific contribution of Prof. Dr. Kiai Ali Mustafa Yaqub, MA to the development of the study of hadith in the archipelago. This paper considers that it is not easy to find people who may be called as a muhaddith (expert of Hadith) within the meaning of its terminology. In fact, the Hadith is the second source of authority (secondary resources) in Islam after the Qur'an. Learning from the figure of Kiai Ali Mustafa Yaqub, every Muslim should know and understand at the same hadith interpret the Hadith, therefore, as it is essential in understanding the contents of the Qur'an. Keyword: Prominent Muslim, Hadith studies, Orientalism, Darus Sunnah, Essay Ulama, Indonesia Studi hadis di Indonesia terlihat masih jarang, kalau tidak dikatakan sangat langka. Hal ini menimbulkan banyak sekali persoalan di tengah-tengah masyarakat Muslim tentang penggunaan hadis-hadis palsu (maudhû’), semi palsu (matrûk), dan lemah (dha’īf), atau mengklaim halhal yang bukan hadis sebagai hadis Nabi. Artikel ini mencoba mengulas latar belakang keilmuan, sumber gagasan pemikiran, dan kontribusi ilmiah Prof. Dr. Kiai Ali Mustafa Yaqub, MA terhadap perkembangan kajian hadis di Nusantara. Tulisan ini beranggapan bahwatidak mudah menemukan orang yang dapat disebut sebagai seorang muhaddis (ahli hadis) dalam arti terminologis. Padahal, hadis adalah sumber otoritas kedua (secondary resources) dalam agama Islam setelah Al-Qur’an. Belajar dari figur Kiai Ali Mustafa Yaqub, setiap muslim sudah seharusnya mengetahui dan memahami hadis sekaligus menginterpretasi ucapan agung Rasulullah SAW tersebut sebagaimana kemestian dalam menghayati isi Al-Qur’an. Keyword: Tokoh Muslim, Kajian Hadis, Orientalisme, Darus Sunnah, Karya Tulis Ulama, Indonesia.